Effects of Macroeconomic Factors on Gross Domestic Product in Nepal - Khatiwada, Sita (Researcher: A Research Journal of Culture and Society, 2020)
The main aim of this paper has tried to find the effect of macroeconomic factors like trade, population growth rate, domestic credit to private sector, and consumer price index on GDP growth using time series data of the last four decades (1975-2018) of Nepal which has been retrieved from a legitimate source of World Bank. This study has used descriptive analysis and multiple linear regression model to access the relationship between predictors and predictand variables. It has been found that there was no significant relationship between GDP growth and macroeconomic factors. This implies that change in any of the variables did not change GDP growth. The finding of the study has suggested the need for more researches with reliable data to find out the causes of economic growth in Nepal.